Interprofessional Approach in Healthcare Services: Its Impact on Patient Safety and Service Quality - Arna, Yessy Dessy; Tulak, Grace Tedy (Oshada, 2026)
The increasing complexity of modern healthcare systems requires integrated and collaborative approaches to ensure patient safety and service quality. Interprofessional collaboration (IPC) has been widely recognized as a strategic response to fragmented care and preventable adverse events. This study aimed to analyze the impact of the interprofessional approach on patient safety and service quality within healthcare institutions. A quantitative cross-sectional design was employed involving 210 healthcare professionals, including physicians, nurses, pharmacists, and allied health workers. Data were collected using validated structured questionnaires measuring interprofessional collaboration, patient safety indicators, and service quality dimensions. Statistical analyses included descriptive statistics, Pearson correlation, multiple regression, and mediation testing. The results revealed that interprofessional collaboration significantly influenced patient safety (β = 0.62, p < 0.001) and service quality (β = 0.31, p < 0.001). Patient safety also significantly predicted service quality (β = 0.49, p < 0.001) and partially mediated the relationship between IPC and service quality (indirect effect β = 0.30, p < 0.01). These findings indicate that IPC enhances healthcare quality both directly and indirectly through strengthened safety mechanisms. In conclusion, strengthening interprofessional collaboration is essential for improving patient safety and achieving sustainable quality enhancement in modern healthcare systems.